2011
DOI: 10.4028/www.scientific.net/amr.306-307.1178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volume Fraction and Temperature on Thermal Conductivity of SiO<sub>2</sub> Nanofluids

Abstract: Thermal conductivities of two kinds of nanofluids (SiO2-water and SiO2-ethylene glycol) were measured by transient hot-wire method at different volume fraction and temperature. Influences of volume fraction of particles and temperature on thermal conductivities of nanofluids were analyzed. The Experimental results show that thermal conductivities of nanofluids are higher than those of base fluids, and increase with the increase of volume fraction and temperature. When approximately 0.5% volume fraction of SiO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There are few reports on SiC, CeO 2 , and SiO 2 nanoparticles reinforcing conventional fluids that confirmed significant decrease on the efficiency of thermal conductivity with respect to increase in particle shapes or sizes [33][34][35][36][37][38][39][40][41][42]. Table 2, Illustrates a summary in enhancement of thermal conductivity of nanoparticles…”
Section: A Thermal Conductivity Property Of Nanofluidsmentioning
confidence: 98%
“…There are few reports on SiC, CeO 2 , and SiO 2 nanoparticles reinforcing conventional fluids that confirmed significant decrease on the efficiency of thermal conductivity with respect to increase in particle shapes or sizes [33][34][35][36][37][38][39][40][41][42]. Table 2, Illustrates a summary in enhancement of thermal conductivity of nanoparticles…”
Section: A Thermal Conductivity Property Of Nanofluidsmentioning
confidence: 98%
“…There have been a few reports on SiC, CeO 2 , and SiO 2 nanoparticles reinforcing conventional fluids that stated a decrease of the effective thermal conductivity with increase in particle size [47,[121][122][123][124][125][126][127][128][129][130][131][132]. Beck et al performed studies on water-based ceria (CeO 2 ) nanofluids [123], which showed an increase in the effective thermal conductivity with an increase of nanoparticle size, although only two particle sizes were studied (12 nm and 74 nm).…”
Section: Nanofiller Sizementioning
confidence: 99%
“…In the past decades, a wide variety of nanoparticles and base fluids have been combined to prepare nanofluids [2][3][4]. A significant amount of experimental and theoretical research has been investigated to understand thermophysical properties of nanofluids [5][6]. Most of previous studies focused on the thermal conductivity and viscosity of various nanofluids [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%